Redemption of the "spoiled identity:" the role of HIV‐positive individuals in HIV care cascade interventions. Issue 4 (6th December 2017) - Camlin, Carol S; Charlebois, Edwin D; Geng, Elvin; Semitala, Fred; Wallenta, Jeanna; Getahun, Monica; Kampiire, Leatitia; Bukusi, Elizabeth A; Sang, Norton; Kwarisiima, Dalsone; Clark, Tamara D; Petersen, Maya L; et al.
Abstract: Introduction: The concept of "therapeutic citizenship" has drawn attention to ways in which public testimony, the "story‐telling in the public sphere" undertaken by people living with HIV (PLHIV), has shaped the global response to the epidemic. This paper presents qualitative findings from two large studies in eastern Africa that reveal how the advent of population‐based HIV testing campaigns and efforts to accelerate antiretroviral "treatment for all" has precipitated a rapidly expanding therapeutic citizenship "project, " or social movement. The title of this paper refers to Goffman's original conceptualization of stigma as a social process through which a person's identity is rendered "spoiled." Methods: Data were derived from qualitative studies embedded within two clinical trials, Sustainable East African Research in Community Health (SEARCH) (NCT# 01864603) in Kenya and Uganda, and START‐ART (NCT# 01810289) in Uganda, which aimed to offer insights into the pathways through which outcomes across the HIV care continuum can be achieved by interventions deployed in the studies, any unanticipated consequences, and factors that influenced implementation. Qualitative in‐depth semi‐structured interviews were conducted among cohorts of adults in 2014 through 2015; across both studies and time periods, 217 interviews were conducted with 166 individuals. Theoretically informed, team‐based analytic approaches were used for the analyses. Results: Narratives from PLHIV, who have not always been conceptualized as actors but rather usually as targets of HIV interventions, revealed strongly emergent themes related to these individuals' use of HIV biomedical resources and discourses to fashion a new, empowered subjecthood. Experiencing the benefits of antiretroviral therapy (ART) emboldens many individuals to transform their "spoiled" identities to attain new, valorized identities as "advocates for ART" in their communities. We propose that the personal revelation of what some refer to as the "gospel of ARVs, " the telling of personal stories about HIV in the public sphere and actions to accompany other PLHIV on their journey into care, is driven by its power to redeem the "spoiled identity:" it permits PLHIV to overcome self‐stigma and regain full personhood within their communities. Conclusions: PLHIV are playing an unanticipated but vital role in the successful implementation of HIV care cascade interventions.